2002
DOI: 10.1046/j.1365-2958.2002.02969.x
|View full text |Cite
|
Sign up to set email alerts
|

The datA locus predominantly contributes to the initiator titration mechanism in the control of replication initiation in Escherichia coli

Abstract: Summary Replication of the Escherichia coli chromosome is initiated synchronously from all origins (oriC) present in a cell at a fixed time in the cell cycle under given steady state culture conditions. A mechanism to ensure the cyclic initiation events operates through the chromosomal site, datA, which titrates exceptionally large amounts of the bacterial initiator protein, DnaA, to prevent overinitiation. Deletion of the datA locus results in extra initiations and altered temporal control of replicatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

7
71
1

Year Published

2006
2006
2020
2020

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 73 publications
(79 citation statements)
references
References 35 publications
7
71
1
Order By: Relevance
“…We observed that datA efficiently hydrolyzed ATP bound to DnaA in a manner dependent on both IHF and Arg285 of the DnaA Argfinger, suggesting that specific DnaA multimer formation is important for DDAH. Deletion of either datA or ihf increased cellular ATP-DnaA levels in a RIDA-independent manner, consistent with the fact that untimely initiations occur in datA and IHF mutant cells (23)(24)(25)27). Because IHF binding to datA in cells was detected specifically at the postinitiation stage, datA function is likely to be temporally regulated.…”
supporting
confidence: 63%
See 3 more Smart Citations
“…We observed that datA efficiently hydrolyzed ATP bound to DnaA in a manner dependent on both IHF and Arg285 of the DnaA Argfinger, suggesting that specific DnaA multimer formation is important for DDAH. Deletion of either datA or ihf increased cellular ATP-DnaA levels in a RIDA-independent manner, consistent with the fact that untimely initiations occur in datA and IHF mutant cells (23)(24)(25)27). Because IHF binding to datA in cells was detected specifically at the postinitiation stage, datA function is likely to be temporally regulated.…”
supporting
confidence: 63%
“…1A), is crucial for repressing untimely initiation events (22)(23)(24)(25). datA-deleted cells, like seqA-deleted cells, perform untimely initiations at a level that does not inhibit cell growth (23).…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…A second level of regulation is mediated by the sequestration of the oriC region by the SeqA protein, which binds with a high affinity to hemimethylated GATC sequences within oriC, thus temporarily restraining reintitiation (6)(7)(8). The third level of initiation control involves the titration of the DnaA protein onto DnaA boxes at the datA locus (9,10). Indeed, datA acts to promote the correct timing of initiation relative to the cell mass (11).…”
mentioning
confidence: 99%